Design of 3D-printed prostheses for reconstruction of periacetabular bone tumors using topology optimization - Zhu, Jiazhuang; Hu, Jianping; Zhu, Kunpeng; Ma, Xiaolong; Wang, Yongjie; Xu, Enjie; Huang, Zhen; Zhu, Yurun; Zhang, Chunlin (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Prostheses for the reconstruction of periacetabular bone tumors are prone to instigate stress shielding. The purpose of this study is to design 3D-printed prostheses with topology optimization (TO) for the reconstruction of periacetabular bone tumors and to add porous structures to reduce stress shielding and facilitate integration between prostheses and host bone.Utilizing patient CT data, we constructed a finite element analysis (FEA) model. Subsequent phases encompassed carrying out TO on the designated area, utilizing the solid isotropic material penalization model (SIMP), and this optimized removal area was replaced with a porous structure. Further analyses included preoperative FEA simulations to comparatively evaluate parameters, including maximum stress, stress distribution, strain energy density (SED), and the relative micromotion of prostheses before and after TO. Furthermore, FEA based on patients' postoperative CT data was conducted again to assess the potential risk of stress shielding subsequent to implantation. Ultimately, preliminary follow-up findings from two patients were documented.In both prostheses, the SED before and after TO increased by 143.61% (from 0.10322 to 0.25145 mJ/mm3) and 35.050% (from 0.30964 to 0.41817 mJ/mm3) respectively, showing significant differences (P<0.001). The peak stress in the Type II prosthesis decreased by 14.494% (from 77.227 to 69.123 MPa), while there was no significant change in peak stress for the Type I prosthesis. There were no significant changes in stress distribution or the proportion of regions with micromotion less than 28 μm before and after TO for either prosthesis. Postoperative FEA verified results showed that the stress in the pelvis and prostheses remained at relatively low levels.The results of follow-up showed that the patients had successful osseointegration and their MSTS scores at the 12th month after surgery were both 100%.These two types of 3D-printed porous prostheses using TO for periacetabular bone tumor reconstruction offer advantages over traditional prostheses by reducing stress shielding and promoting osseointegration, while maintaining the original stiffness of the prosthesis. Furthermore, in vivo experiments show that these prostheses meet the requirements for daily activities of patients. This study provides a valuable reference for the design of future periacetabular bone tumor reconstruction prostheses.